Implications of Stochastic Transmission Rates for Managing Pandemic Risks - Hong, Harrison; Wang, Neng; Yang, Jinqiang (Review of Financial Studies, 2021)
Abstract We introduce aggregate transmission shocks to an epidemic model and link firm valuations to infections via an asset pricing framework with vaccines. Infections lower earnings growth but firms can mitigate damages. We estimate a large reproduction number $\ mathcal R_0$ and transmission volatility for COVID-19. Using these estimates, we quantify the bias of deterministic approximations based on $\ mathcal R_0$. Our model generates predictions consistent with the data: unexpected infection resurgence, nonmonotonic mitigation policies, and higher price-to-earnings ratios during a pandemic. Valuations would be significantly lower absent mitigation and a high vaccine arrival rate.